ANALYSIS OF FACTORS INFLUENCING M1 APPLE MACBOOK PURCHASE INTENTION USING BINARY LOGISTIC REGRESSION - Oktarini, Dwi Indah; Wicaksono, Muhammad Haston Samudra; Putri, Juandela Herina; Heikal, Jerry (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
In today's modern era, technology is developing every year with various new technological discoveries. One of the leading technology manufacturing companies is Apple. Apple Inc. is a computer company founded by Steve Jobs and Steve Wozniak on April 1, 1976 and was originally named Apple Computer because it only produced personal computers, computer peripherals, and computer software in America. The MacBook, Apple's iconic laptop, has revolutionized the world of personal computing since its debut in 2006. In 2021, there was a phenomenon of the largest revenue record of all time in Q1 2021 after the release of the Apple Macbook M1 where Mac revenue jumped by 70 percent. Based on this background, this study was conducted to determine the factors that influence the purchasing behavior of the Macbook M1 in order to carry out future product development strategies. The data used was taken from Kaggle.com with a population of 133. The method used is the Binary Logistic Regression method using SPSS. The results of this study indicate that there are three very significant factors influencing the purchasing behavior of the M1 MacBook, namely the variables Brand trust, performance, and M1 Chipset with the percentage of the correctness of the model reaching an average of 74.4% to be able to predict purchasing behavior. So the recommendations that Apple can do to carry out future product development strategies are to increase and maintain brand trust, increase performance, and explore and develop the M1 Chipset.